2020
DOI: 10.32799/ijih.v16i2.33206
|View full text |Cite
|
Sign up to set email alerts
|

Letsemot, “Togetherness”: Exploring How Connection to Land, Water, and Territory Influences Health and Wellness with First Nations Knowledge Keepers and Youth in the Fraser Salish Region of British Columbia

Abstract: Connection to land has been identified as a central determinant of the health and well-being of First Nations in Canada. The wholistic, interconnected, spiritual, and sacred relationship that many Indigenous Peoples have with the land is an integral part of strengthening physical, spiritual, mental, and emotional health and well-being. However, there has been little empirical evidence on how to assess, measure, and report on connection to land for First Nations Peoples. Using a Two- Eyed S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…This theme was divided into four sub-themes including: (a) analysis results presented to an Indigenous advisory group for feedback and comment, (b) Indigenous community member(s) involved with coding and analysis, (c) analysis results reviewed with research participants via member checking, and (d) partnership with an Elder or Knowledge Keeper during analysis. Member checking with research participants was the most commonly used strategy to involve Indigenous community members representing nearly half ( n = 15/32; 47%) of the articles (Carter et al, 2017; Danto et al, 2021; Hatala et al, 2020; Latimer et al, 2020; Marsh et al, 2015; Martin et al, 2017, 2018; Quinn, 2022; Rand, 2016; Rowan et al, 2015; Stelkia et al, 2021; Vorobyova et al, 2022; Whiting et al, 2018; Whitty-Rogers et al, 2016; Wright et al, 2019). According to Marsh et al (2015), transparency and member checking is grounded in the Two-Eyed Seeing Indigenous decolonizing approach and Aboriginal research ethics/protocol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This theme was divided into four sub-themes including: (a) analysis results presented to an Indigenous advisory group for feedback and comment, (b) Indigenous community member(s) involved with coding and analysis, (c) analysis results reviewed with research participants via member checking, and (d) partnership with an Elder or Knowledge Keeper during analysis. Member checking with research participants was the most commonly used strategy to involve Indigenous community members representing nearly half ( n = 15/32; 47%) of the articles (Carter et al, 2017; Danto et al, 2021; Hatala et al, 2020; Latimer et al, 2020; Marsh et al, 2015; Martin et al, 2017, 2018; Quinn, 2022; Rand, 2016; Rowan et al, 2015; Stelkia et al, 2021; Vorobyova et al, 2022; Whiting et al, 2018; Whitty-Rogers et al, 2016; Wright et al, 2019). According to Marsh et al (2015), transparency and member checking is grounded in the Two-Eyed Seeing Indigenous decolonizing approach and Aboriginal research ethics/protocol.…”
Section: Resultsmentioning
confidence: 99%
“…Involvement of an Indigenous community member with the coding and analysis process was the next most common strategy ( n = 9/32; 28%) (Bruner et al, 2019; Galway et al, 2022; Hunt et al, 2018; Latimer et al, 2020; Marsh et al, 2015; VanEvery et al, 2022; Vorobyova et al, 2022; Ward et al, 2023; Wright et al, 2019). Finally, analysis in partnership with an Elder or Knowledge Keeper was the last strategy ( n = 7/32; 23%) (Clark, 2014; Hall et al, 2015; Jackline et al, 2020; Kurtz et al, 2017; Latimer et al, 2020; Rowan et al, 2015; Stelkia et al, 2021). One article identified that the Elder was part of the research team (Stelkia et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Barriers that impact health access are rooted in racism and discrimination. In Canada, racism remains a key determinant of health and signi cantly impacts Indigenous Peoples access to non-Indigenous-led health services and is well documented in reports such as the British Columbia (BC) Commissioned In Plain Sight report (7,10,11). The impacts of the COVID-19 pandemic have left gaps in knowledge that are not only essential to address now but also in preparation for future pandemic planning in the health system.…”
Section: Introductionmentioning
confidence: 99%
“…This can be one's interconnection with spirit, land, people, animals, and plants, including how such entities co-exist together in a shared environment. Land-based activities emphasize the connectivity within these relationships, and situate an individual within meaningful culturally and spiritually significant contexts [5]. It is this spiritual significance of engaging in land-based activities that differentiates these approaches from other nature-focused activities or programs, which can have similar psychological benefits, but do not emphasize connection to place or cultural significance [6].…”
Section: Introductionmentioning
confidence: 99%